Needle size for thyroid fine needle aspiration cytology. A single institution experience - Cianci, Pasquale; Tumolo, Rocco; Conversano, Ivana; Travaglia, Damiano; Trigiante, Giuseppe; Lantone, Giuliano; Lizzi, Vincenzo; Cappiello, Miriam; Montagna, Marco; Curci, Fabio Pio; Restini, Enrico (Frontiers in Surgery, 2024)
Background Fine needle aspiration cytology (FNAC) is an invasive diagnostic technique which is widely used for the cytological diagnosis of thyroid nodules. This procedure is generally widely tolerated by patients, albeit often accompanied by local pain and discomfort. Despite various proposals of execution methods, no approach is universally accepted,especially regarding the size of the needle to be used for sampling. Needle gauge preferences vary across regions, with 25-gauge needles more common in Western countries and 22-gauge needles favored in Asian countries. Complications associated with larger needles have been studied but remain inconclusive. Materials and methods Over one year, we conducted 300 FNAC procedures under ultrasound guidance, employing both 22-gauge and 25-gauge needles. In no patient was local anesthesia performed before starting the procedure, which in all was performed by the same operator. Similarly the cytological examination of the material taken was performed by a single operator. Patients, 105 males and 195 females, were divided into two groups of 150 each based on the needle size used. Results Patients treated with 22-gauge needles reported higher levels of pain during the procedure and increased discomfort afterward. Similarly, a greater incidence of hematomas and vasovagal reactions was noted in this group. However, the cell sample obtained and diagnostic response rates were consistent across both groups. Conclusion On the basis of our observations we concluded that the size of the needle used is irrelevant for the purposes of the diagnostic result, as long as the procedure is performed by expert personnel. However, the 25-gauge needle is preferable because it's more tolerated and accepted by patients. Our results do not represent a single and conclusive verdict, but they could represent the starting point for further research.